การประเมินความสัมพันธ์ทางพันธุกรรมของพืชครามสกุล Indigofera ด้วยลำดับนิวคลีโอไทด์ของยีน rpoC1 และชิ้นดีเอ็นเอระหว่างยีน trnH กับ psbA - ธนานันต์ นฤมล; ปาลวัฒน์ ณัฐพล; บัวบาน ศุภรัตน์; ศากยวงศ์ นิรมล; ธนานันต์ ธีระชัย (Thai Journal of Science and Technology, 2021)
Indigofera, a plant in the Leguminosae, is an essential plant in fabric dyes production and has some pharmacological properties. This research aims to identify 15 Indigofera species using nucleotide sequences of rpoC1 genes and DNA fragments between trnH and psbA genes. Comparing nucleotide sequences data in NCBI database can identify Indigofera species and outgroup plants. When analyzed with the ClustalW program and a phylogenetic tree was constructed using UPGMA method by MEGA X program. All of the samples were classified into two groups. Sample No. 4 could be identified as Indigofera tinctoria and sample No. 13 (outgroup) could be identified as Vigna angularis. This research can be used as information for the conservation and improvement of Indigofera breeding.